INSOMNIA - Nor Syazwani Binti Abdul Samad; Nyoman Ratep; Wayan Westa (Bali Journal of Medical and Health Sciences, 2013)
Insomnia is one of the more common complaints patients present to their physicians. Sleep problems affect up to one-third of all Americans, and the loss of workplace productivity. Patients with acute insomnia generally respond well to various sedative hypnotic medications, but chronic insomnia is a different challenge. Physicians and patients may raise concerns about the long-term use of sedative hypnotic medications. Even in light of these concerns, however, the chronic insomnia remains, ostensibly leaving the physician few choices. A number of promising nonpharmacologic strategies are available that physicians can easily implement. Through the use of selfrating instruments and a sleep log, physicians can bring the sleep problem into better focus and monitor the efficacy of clinical interventions. Certain behavioral techniques, such as sleep hygiene, stimulus control, and sleep restriction, can be effective remedies for chronic insomnia. The use of cranial electric stimulation for insomnia is also showing promising results. Through careful assessment and the adoption of simple nonpharmacologic strategies, the physician’s interventions may result in a good night’s sleep.